Analisis Penerapan Lean Production Process untuk Mengurangi Lead Time Process Perawatan Engine (Studi Kasus PT.GMF AEROASIA) - Wahyu Adrianto; Muhammad Kholil (Jurnal Optimasi Sistem Industri, 2015)
Engine maintenance strives to always improve its service excellence with tools such as gate system where the system is expected to realize the lead time for 60days. In the implementation of the gate system is still not able to meet the expected target. During maintenance or overhaul the engine is still encountered waste or waste that causes the target cannot be met. Lean Manufacturing is an approach that aims to minimize waste that occurs in the process flow.Understanding the conditions of the process described in Value Stream Mapping for further elaborate activities that have the value-added and non-value added.Through seven waste concept, then be weighted to determine the most dominant type of waste.From the data processing is obtained that through the Value Stream Mapping is known gate 1 and gate 3 is the point that there are many wastes. Weighting and ranking of seven existing waste in the process of the activity obtained results in the form of a waste critical sequence of seven existing waste. Highest weights on the type of waste waiting with a weight of 0.38. Results of Root Cause Analysis in mind that the root cause of waste waiting for that data is maintained, the lack of attention to people development, There are still bugs in the system and miscommunication.